2020
DOI: 10.1111/jdv.16565
|View full text |Cite
|
Sign up to set email alerts
|

Dermatology consultation service at a large metropolitan hospital system serving minority populations

Abstract: Background Dermatology consultations in the inpatient hospital setting can improve diagnostic accuracy and management. Objective Characterize dermatologic diagnostic and treatment trends in the hospital setting and identify variables that may affect patient care. Methods Retrospective chart review from 1 January 2012 to 31 December 2017 at Jackson Memorial Hospital (JMH) (Miami, Florida, USA), an academic non‐profit tertiary care centre affiliated with University of Miami Miller School of Medicine, was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 17 publications
11
24
0
Order By: Relevance
“…Almost all of these indications were common skin disorders, none of them were rare diagnosis. The inflammatory skin disorders and cutaneous infections have been reported to be most common clinical diagnoses in dermatology consultations in most of the large hospital series before COVID pandemic similar with our study 3 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Almost all of these indications were common skin disorders, none of them were rare diagnosis. The inflammatory skin disorders and cutaneous infections have been reported to be most common clinical diagnoses in dermatology consultations in most of the large hospital series before COVID pandemic similar with our study 3 …”
Section: Discussionsupporting
confidence: 91%
“…The role of dermatology consultations have been reviewed in many large hospital centers either in different departments such as emergency, hematology and transplantation units or in different indications selecting only one category such as inflammatory disorders or cutaneous infections 3‐6 In our study skin disorders were classified into several subgroups according to their etiology and it was seen that the most common consultation requests were made by COVID services including wards and intensive care unit (n = 54, 32.5%).…”
Section: Discussionmentioning
confidence: 83%
“…Dermatology is primarily an outpatient-based service; however, dermatologists also play essential roles in providing dermatology consultations to inpatients hospitalized for care in other speciality disciplines [1,2]. Timely and accurate dermatology consultations can benefit the hospitalized patients in terms of diagnosis and treatment of skin diseases [3,4]. A retrospective study of 731 referrals for dermatology consultations showed that there was not always a good correspondence between the provisional diagnoses made by the referring doctors and the final diagnoses confirmed by dermatologists, with 30.2% correct diagnoses, 35.2% incorrect diagnoses, and 34.6% no provisional diagnoses [5].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnoses of skin diseases were made according to the International Classification of Disease, 10th Revision. Diseases were classified by two of the authors (HZ and KT) according to previously published articles on inpatient dermatology consultations [2,4,10,12], and the classification was re-checked by another two authors (HJ and QS, both professors in dermatology). This study was approved by the Institutional Review Board at Peking Union Medical College Hospital (Number: S-K1589).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] These patients account for a variable proportion of consultations, with Fayne et al's finding just 0.7% of consultations were from hematology/ oncology services and Tracey et al's finding 23% from bone marrow transplant services. 5,9 The objective of our study was to investigate the role of dermatologists in the care of hospitalized…”
Section: Introductionmentioning
confidence: 99%